Evaluating Mixed Methods in The Pragmatic Analysis of The Nasi Hadap-Hadapan Tradition In Batubara, Indonesia - Fadli, Izhar; Fithriani, Rahmah; Mukminin, Amirul (ITScience (Information Technology and Science), 2025)
The Nasi Hadap-Hadapan tradition is a significant ceremonial practice of the Batubara community in North Sumatra, Indonesia, characterized by symbolic actions and culturally embedded communication. Despite its rich communicative features, this tradition has not been thoroughly examined through a pragmatic linguistic lens, particularly using a mixed method approach. This study aims to evaluate the effectiveness of the exploratory sequential mixed method in analyzing the forms, functions, and meanings of speech acts within the Nasi Adap-Adapan tradition. The qualitative phase involved participatory observation and in-depth interviews with traditional leaders and ceremony participants to identify pragmatic patterns and sociocultural meanings. The quantitative phase analyzed 145 speech acts transcribed from video recordings, categorized into five types based on Searle’s classification: expressive, directive, representative, commissive, and declarative. The findings revealed that expressive (33.8%) and directive (28.3%) speech acts were the most dominant, emphasizing the ceremony’s function in fostering emotional bonds and guiding ritual procedures. These acts were embedded within cultural symbols, such as food offerings and customary phrases. The mixed method approach proved effective in capturing both the linguistic structure and sociocultural context of ceremonial communication. This study highlights the importance of integrated methodologies in pragmatic research, particularly in documenting and analyzing traditional oral practices within non-Western cultural contexts. Keywords: mixed method, pragmatic analysis, speech acts, cultural tradition, Batubara community